2018
DOI: 10.1083/jcb.201712058
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomal YKT6 is required for fusion with lysosomes independently of syntaxin 17

Abstract: Macroautophagy is an evolutionarily conserved catabolic mechanism that delivers intracellular constituents to lysosomes using autophagosomes. To achieve degradation, lysosomes must fuse with closed autophagosomes. We previously reported that the soluble -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein syntaxin (STX) 17 translocates to autophagosomes to mediate fusion with lysosomes. In this study, we report an additional mechanism. We found that autophagosome-lysosome fusion is reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
196
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 50 publications
9
196
1
1
Order By: Relevance
“…Recent studies have uncovered the yeast SNARE, Ykt6, as important in autophagosome-vacuole/lysosome fusion in yeast (Bas et al, 2018;Gao et al, 2018), and that mammalian Ykt6 ortholog (Matsui et al, 2018;Takats et al, 2018) plays a potentially dominant (over Stx17) role in mammalian autophagosome-lysosome fusion. Whereas the exact mechanism of Ykt6 in maturation has not been agreed upon, with differences in proposed models (Matsui et al, 2018;Takats et al, 2018), it is worth noting that Ykt6 is also part of one of the retrograde trafficking routes from endosomes to TGN that includes GOS-28/ GOSR1 (Tai et al, 2004), an mAtg8-binding SNARE as discussed above. Nevertheless, our data here suggest that Stx17 still plays a very important role in autophagosomal flux, revealed in the requirement for a STX16/STX17 double KO to block autophagic flux using the conventional and well-accepted LC3 flux assay (Klionsky et al, 2016), and reflected in autophagic degradation of a diverse panel of substrates: mitochondria, peroxisomes, M. tuberculosis, and ribosomes.…”
Section: B Validation Of Stx16/stx17 Dko By Western Blot Analysis In mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have uncovered the yeast SNARE, Ykt6, as important in autophagosome-vacuole/lysosome fusion in yeast (Bas et al, 2018;Gao et al, 2018), and that mammalian Ykt6 ortholog (Matsui et al, 2018;Takats et al, 2018) plays a potentially dominant (over Stx17) role in mammalian autophagosome-lysosome fusion. Whereas the exact mechanism of Ykt6 in maturation has not been agreed upon, with differences in proposed models (Matsui et al, 2018;Takats et al, 2018), it is worth noting that Ykt6 is also part of one of the retrograde trafficking routes from endosomes to TGN that includes GOS-28/ GOSR1 (Tai et al, 2004), an mAtg8-binding SNARE as discussed above. Nevertheless, our data here suggest that Stx17 still plays a very important role in autophagosomal flux, revealed in the requirement for a STX16/STX17 double KO to block autophagic flux using the conventional and well-accepted LC3 flux assay (Klionsky et al, 2016), and reflected in autophagic degradation of a diverse panel of substrates: mitochondria, peroxisomes, M. tuberculosis, and ribosomes.…”
Section: B Validation Of Stx16/stx17 Dko By Western Blot Analysis In mentioning
confidence: 99%
“…In the context of autophagy, SNAREs have been studied at different stages along the autophagy pathway (Nair et al, 2011;Itakura et al, 2012;Moreau et al, 2013;Kimura et al, 2017). Recent studies have indicated that additional SNAREs may be required or even be dominant in this process (Matsui et al, 2018;Takats et al, 2018). Recent studies have indicated that additional SNAREs may be required or even be dominant in this process (Matsui et al, 2018;Takats et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they strongly suggest that membrane-anchored Atg8 proteins can trigger only a reversible membrane tethering reaction by themselves but not mediate an irreversible hemifusion or fusion events when any other protein components are not present. Additional fusogenic proteins acting together with Atg8 proteins may include autophagy-related SNARE-family proteins that have been reported to be targeted to autophagic compartments and involved in autophagosome formation and maturation [22,[48][49][50]. However, it should be noted that, since membrane attachment of cytosolic Atg8 proteins via the conjugation to a nonlamellar-prone PE lipid is proposed to take place at locally-curved unstable lipid bilayers [45,46,51], we will not exclude the possibility that the intrinsic fusogenic potency of membrane-anchored Atg8 proteins directly facilitate membrane fusion events specifically at the highly-curved, fusion-prone membrane segments of autophagic compartments, including the rim of the cup-shaped phagophore membrane.…”
Section: Trans-assembly Of Human Atg8 Proteins Can Drive Membrane Tetmentioning
confidence: 99%
“…YKT6 presents multiple domains required for its intracellular localization and the N‐terminal longin domain has been found to be necessary for its localization to autophagosomes. At the autophagosome–lysosome interface, YKT6 interacts with SNAP29 and with the lysosomal SNARE STX7 .…”
Section: The Autophagy Pathway: Autophagosome Biogenesis Maturationmentioning
confidence: 99%